Risk as a wicked problem in planning: the role of future non-knowledge - Stufano Melone, Maria Rosaria; Camarda, Domenico (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Dealing with spatial organization, planning and design has to cope with something that is not (not yet or never will be) there. This is a matter of knowledge and of knowledge management, a matter for times to come: so in knowledge management the facet of non-knowledge appears. The research reflections proposed here are connected with activities carried out in the case study of Biccari, a small village in the north of Puglia (Italy), located on the slopes of the Dauni Mountains, between the Apulian plateau and fragile mountain terrains. It involved the University of Sannio and the Polytechnic University of Bari, to provide scientific support aimed at drawing up the town’s master plan (PUG). The territory is affected by an extensive paleolandslide, creating significant hydrogeological risk conditions. Despite this, the local community tends to remove such risk from their perception, showing fatalistic attitudes toward phenomena considered inevitable. The paper explores how to deal with “non-knowledge” in spatial planning, particularly by integrating local risk perceptions and decision-making dynamics into agent-based simulation models developed using NetLogo software. As an exploratory study, it proposes a prototype framework to simulate interactions between institutional decisions, environmental dynamics and community behaviors, with the goal of supporting more adaptive, informed and resilient planning strategies – managing uncertainty as a constitutive element of planning in fragile territories, rather than as a problem to be eliminated.